2000
DOI: 10.1211/0022357001773814
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti-inflammatory Effect of Chalcones

Abstract: The process of degranulation of mast cells and neutrophils contributes to inflammatory disorders. Activation of microglial cells and macrophages is believed to be involved in inflammatory, infectious and degenerative diseases of the CNS. Combining the potent inhibition of chemical mediators released by the degranulation of mast cells or neutrophils and from the activated microglial cells or macrophages, would lead to a promising anti-inflammatory agent for the treatment of peripheral and central inflammation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
128
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(133 citation statements)
references
References 19 publications
(18 reference statements)
3
128
0
2
Order By: Relevance
“…Previously, it was demonstrated that hydroalchoolic stem bark extracts from M. urundeuva exert anti-inflammatory effects attributed to chalcones , Souza et al 2007), a compound belonging to the group of flavonoids naturally found in fruits, flowers, vegetables, teas and wines (Abdulla andGruber 2000, Ferreira et al 2008). Besides the traditional antioxidant properties attributed to the flavonoids, some chalcones and their derivatives have reported to be potent cyclooxygenase inhibitors (Hsieh et al 1998). This is an important approach to some kinds of cancers, since COX-2 blockage avoids the expression of NF-κB activation, a key nuclear transcription factor involved in controlling inflammation and tumorigenesis (Surh et al 2001), since inflammation has been frequently found in premalignant lesions (Dranoff 2004).…”
mentioning
confidence: 99%
“…Previously, it was demonstrated that hydroalchoolic stem bark extracts from M. urundeuva exert anti-inflammatory effects attributed to chalcones , Souza et al 2007), a compound belonging to the group of flavonoids naturally found in fruits, flowers, vegetables, teas and wines (Abdulla andGruber 2000, Ferreira et al 2008). Besides the traditional antioxidant properties attributed to the flavonoids, some chalcones and their derivatives have reported to be potent cyclooxygenase inhibitors (Hsieh et al 1998). This is an important approach to some kinds of cancers, since COX-2 blockage avoids the expression of NF-κB activation, a key nuclear transcription factor involved in controlling inflammation and tumorigenesis (Surh et al 2001), since inflammation has been frequently found in premalignant lesions (Dranoff 2004).…”
mentioning
confidence: 99%
“…21−23 Moreover, various drugs containing a pyrimidine nucleus like 5-fluorouracil (5-FU), tegafur, and thioguanine were prepared and used as anticancer agents. 24,25 Chalcones are known to show different biological activities, such as antioxidant, 26 antiinflammatory, 27 antimalarial, 28 antileishmanial, 29 anticancer, 30 and antitumor 31 activities.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcones are a class of compounds mostly studied for pharmacological properties 10,11 and recently have been explored for their optical applications [12][13][14][15] . In the past few years chalcones have been shown to possess interesting biological properties like anti-invasive 16 , anticancer 17,18 , antimalarial 19 , antimicrobial 20 , antimutagenic 21 , radioprotective 22 , anti-inflammatory effects 23 and find use as synthetic intermediates 24 .…”
Section: Introductionmentioning
confidence: 99%